М.ЖУМАНАЗАРОВА ҲӘМ П.МЫРЗАБАЕВАНЫҢ ФИЛОСОФИЯЛЫҚ-ИНТЕЛЛЕКТУАЛЛЫҚ ЛИРИКАСЫНДА ЛИРИКАЛЫҚ ХАРАКТЕРДИҢ ЖАРАТЫЛЫЎ ӨЗГЕШЕЛИГИ - Алиева, Х.Р. (FAN va JAMIYAT, 2023)
This article examines the philosophical-intellectual lyrics and the lyrical hero in the works of poetess M.Jumanazarova and P.Mirzabaeva.